Fluctuations in perceived energy and mood among patients with chronic fatigue syndrome - Wood, C; Magnello, M; Sharpe, M (1992)
Patients currently suffering or recently recovered from chronic fatigue syndrome (CFS) were compared with each other and with a group of well-matched controls in a study of diurnal variation in levels of perceived mental and physical energy and positive and negative affect. Patients who were currently ill showed diurnal variation in patterns of energy, with maximum levels being recorded between 10.00 h and 12.00 h which were significantly higher (P < 0.05) than energy levels recorded on rising or retiring. This pattern was similar to the controls but average energy levels at each time point were lower (P < 0.05) among the ill patients. Recovered patients showed the same pattern, with mean energy levels falling between those of the ill patients and controls. Similar diurnal patterns were found for perceptions of positive, though not negative affect. Correlations between physical and mental energy and between both of these energy variables and positive affect were high (r = 0.75 to 0.85) in both controls and CFS patients. However, correlations with negative affect were low (eg r = -0.10) and non-significant. Total scores on the Hospital Anxiety and Depression Scale (HAD) were significantly higher (P < 0.05) among patients who were still ill than those who had recovered. Scores on the HAD Depression (but not Anxiety) subscale were also significantly higher among those who were still ill (P < 0.01). These findings may be of value in facilitating programmes of cognitive-behavioural modification intended to aid the recovery of patients with CFS.